Literacy outcomes for students with speech impairment: long-term follow up - Leitao, Suze; Fletcher, J. (Taylor & Francis Ltd, 2004)
Background: Theoretical and empirical support now exists for the finding that many children with expressive phonological impairment experience problems in acquiring phonological awareness and early literacy skills. Few studies, however, have examined the long-term academic and literacy outcomes for this population, in particular as the students leave the final stages of primary school. Aims: The reported study forms the final stage of a longitudinal research project that tracked the phonological processing and literacy skills of a group of children with specific speech impairment from their first year at school (aged 5–6 years). The earlier data provided evidence of a relationship between speech impairment characterized by the presence of non-developmental error processes and weaker phonological awareness and literacy skills in the first 2–3 years at school. It was hypothesized that the effect of this relationship would continue to be apparent as the students completed the final stages of primary school. Methods & Procedures: Fourteen of the original set of 36 students were available for reassessment of their phonological processing, reading and spelling skills at age 12–13 years.Outcomes & Results: Those children with an original classification of non-developmental speech errors performed significantly more poorly than those with an original classification of developmental errors on phonological awareness and reading comprehension measures. Reading accuracy and spelling scores also showing a similar trend. Conclusions: These findings provide further evidence for the long-term impact of speech impairment. The follow-up data demonstrated ongoing difficulties for students who entered school with expressive speech impairment, particularly those whose speech errors were characterized by non-developmental error processes. The impact was apparent on tasks measuring phonological awareness, reading accuracy and spelling (skills that depend on good phonological processing skills and clear underlying phonological representations). Weaknesses in reading comprehension were also found. These findings have implications for the early identification of those at risk. In addition, intervention approaches for young children with expressive speech difficulties demonstrating these patterns of error should address weak underlying phonological representations and develop phonological awareness skills.